Literature Review : In Silico Study Of Lung Anticancer Proteins - Alya Nafis; Fajar Prasetyo; Nur Sa’diyyah; Deviana Farhani; Nur Aenah (Sean Institute, 2023)
Cancer is a disease caused by rapid and uncontrolled cell proliferation. Cancer is a massive disease characterized by rapid and uncontrolled cell proliferation. Cancer cells will continue to affect other cells around them until all tissues with cancer damage organs and nerves. One type of cancer with high cases in Indonesia is lung cancer. This cancer is a type of tumor whose source is the epithelial lining of the bronchial lung branches. Generally, therapy for the treatment of lung cancer is radiation, chemotherapy, surgery, and hormone therapy. In silico testing is a type of study with a computational approach to predict the activity of potential compounds as drugs. This article uses a type of literature review research with a total of 15 reference materials indexed on Google Scholar.